If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -11 = 6x + 3 Reorder the terms: -11 + 2x = 6x + 3 Reorder the terms: -11 + 2x = 3 + 6x Solving -11 + 2x = 3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -11 + 2x + -6x = 3 + 6x + -6x Combine like terms: 2x + -6x = -4x -11 + -4x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 -11 + -4x = 3 + 0 -11 + -4x = 3 Add '11' to each side of the equation. -11 + 11 + -4x = 3 + 11 Combine like terms: -11 + 11 = 0 0 + -4x = 3 + 11 -4x = 3 + 11 Combine like terms: 3 + 11 = 14 -4x = 14 Divide each side by '-4'. x = -3.5 Simplifying x = -3.5
| y-7=1.5-6 | | 2n-6-=-8n+14 | | -6p+20=-3p-18-5p | | 8x^2+21+0=0 | | -3.6(2y-6)+2.9y= | | -3+8n=7+10n | | 10-b=-6b-10+9b | | 8(-2k+6)+4k=38-7k | | 12x-40xy= | | a=f(a+b) | | 3d-4=10+5d | | 7x+3+-2x+14= | | -3(X+4)+15=-14 | | -2y=-y-6 | | 6a-7=2(3a+5) | | 10-5z=-3z-10 | | F+V-E= | | 3(7s+6)-17s=2(2s+5)-15 | | -7+4t=5t | | m^2-m-42=0 | | -4k-10=k | | 96-1x=82 | | 4x^2+2x^3+18=0 | | 8.1-13.5=2.9 | | x/20x+1=10-3/1 | | 0.33333(6+9t)=5t-20 | | 4x^2-12x=36 | | -2w-10=10-4w | | -3+11=2 | | 5d+7=4d-9 | | 7(5a-4)-1=-8a | | -4(b-1)=-b-27 |